Asymmetry in elite rowers: effect of ergometer design and stroke rate - Fohanno, V.; Nordez, A.; Smith, R.; Colloud, F. (Sports Biomechanics, 2015)
Between limb movement asymmetries and foot force production asymmetries are thought to be detrimental for both rower's performance and risk of injury, particularly when rowing frequently on ergometers. Several ergometers with different designs can be used by rowers as part of their indoor training. Hence, this study aimed to compare asymmetries in lower limb joint kinematics and foot force production with respect to ergometer design and rowing intensity. A new symmetry index was proposed to assess these asymmetries in elite rowers during a test on three ergometers. Additionally, the asymmetry in lower limb length was assessed to investigate its relationship with kinematic and kinetic asymmetries. Parameters describing medium (5-10%) or high (>10%) asymmetries were compared between rowing ergometers and intensities. Results indicated medium asymmetries for the ankle joint angle and hip-knee joint accelerations and high asymmetries for the resultant force and the ankle joint acceleration associated with a low inter-stroke variability. Kinetic asymmetry was neither correlated to kinematic asymmetry nor with lower limb length asymmetry. The use of a mobile ergometer led to higher joint acceleration asymmetries. Further studies are necessary to investigate the relation between these findings and muscular adaptations that may increase the risk of lower-back injury.